Characterization of lysine acetyltransferase and deacetylase genes and their roles in anthocyanin biosynthesis in grape - Wen Tang; Feiyue Li; Danni Yang; Mengyu Xu; Jinggui Fang; Suwen Lu (Horticulture Advances)
Abstract Lysine acetylation is pivotal in regulating growth, development, and stress responses across numerous plant species. This modification, mediated by lysine acetyltransferases (KATs) and lysine deacetylases (KDACs), is both dynamic and reversible. Despite the economic significance of grape (Vitis vinifera) as a fruit crop, comprehensive insights into its KAT and KDAC gene families remain limited. In this study, 8 VvKATs and 14 VvKDACs were identified within the grape genome. Detailed analyses of their physicochemical properties, chromosomal distribution, phylogenetic synteny, evolutionary relationships, gene structures, and conserved motifs were conducted. Promoter region analysis revealed numerous cis-regulatory elements linked to light, hormone, and stress responsiveness. Transcriptomic data indicated that VvKATs and VvKDACs display distinct expression profiles across various tissues and developmental stages. Notably, VvSRT1, VvHDA19a, and VvHDA15 expression levels correlated strongly with anthocyanin accumulation in grape. Application of the deacetylase inhibitor sirtinol resulted in berry color changes and increased anthocyanin accumulation, suggesting that enhanced anthocyanin content in sirtinol-treated grape berry skins may result from post-translational modifications of genes involved in anthocyanin biosynthesis. These findings contribute to a deeper understanding of VvKAT and VvKDAC gene structures and properties, establishing a foundation for further exploration into lysine acetylation's role in fruit quality, particularly anthocyanin biosynthesis, in grape.